Visualizing changes in electron distribution in coupled chains of cytochrome bc(1) by modifying barrier for electron transfer between the FeS cluster and heme c(1) - Cieluch, Ewelina (Elsevier Pub. Co, 2010)
Cytochrome c(1) of Rhodobacter (Rba.) species provides a series of mutants which change barriers for electron transfer through the cofactor chains of cytochrome bc(1) by modifying heme c(1) redox midpoint potential. Analysis of post-flash electron distribution in such systems can provide useful information about the contribution of individual reactions to the overall electron flow. In Rba. capsulatus, the non-functional low-potential forms of cytochrome c(1) which are devoid of the disulfide bond naturally present in this protein revert spontaneously by introducing a second-site suppression (mutation A181T) that brings the potential of heme c(1) back to the functionally high levels, yet maintains it some 100 mV lower from the native value. Here we report that the disulfide and the mutation A181T can coexist in one protein but the mutation exerts a dominant effect on the redox properties of heme c(1) and the potential remains at the same lower value as in the disulfide-free form. This establishes effective means to modify a barrier for electron transfer between the FeS cluster and heme c(1) without breaking disulfide. A comparison of the flash-induced electron transfers in native and mutated cytochrome bc(1) revealed significant differences in the post-flash equilibrium distribution of electrons only when the connection of the chains with the quinone pool was interrupted at the level of either of the catalytic sites by the use of specific inhibitors, antimycin or myxothiazol. In the non-inhibited system no such differences were observed. We explain the results using a kinetic model in which a shift in the equilibrium of one reaction influences the equilibrium of all remaining reactions in the cofactor chains. It follows a rather simple description in which the direction of electron flow through the coupled chains of cytochrome bc(1) exclusively depends on the rates of all reversible partial reactions, including the Q/QH(2) exchange rate to/from the catalytic sites.